A new structural model for the study of adult playfulness: Assessment and exploration of an understudied individual differences variable. (1st April 2017) - Proyer, René T.
Abstract: Adult playfulness is an understudied personality trait. A new 28-item questionnaire (the OLIW) is proposed that assesses four basic components; namely, Other-directed, Lighthearted, Intellectual, and Whimsical playfulness. Study 1 provides support for the factorial validity in an Exploratory ( N = 628) and a Confirmatory Factor Analysis ( N = 1168). Item- and scale-statistics were satisfactory. Correlations in the expected range with other playfulness questionnaires provide support for the convergent validity of the scale; there was between 3 and 30% shared variance with the big five personality traits. Test-retest reliabilities were between 0.67 and 0.87 for one-week, two-week, one-month, and three-month intervals ( N = 200; using a reduced set of 12 items). Study 2 found convergence between self- and peer-reports in the expected range (i.e., 44–0.57). Participants in Study 3 ( N = 295) collected daily behavior ratings for 14 days for Play, Aggression, Exhibitionism, and Impulsivity, and completed respective trait measures on day one. The OLIW demonstrated correlations between 0.29 and 0.36 for the aggregated behavior ratings, which was in the expected range. Overall, the findings for the psychometrics, reliability (internal consistency, test-retest), and validity (factorial, convergent, discriminant) are satisfactory and further use of the OLIW is encouraged. Highlights: A new structural model of adult playfulness and its measurement is introduced. 4-facets: Other-directed, Lighthearted, Intellectual, and Whimsical . The scale (OLIW) has good psychometric properties and encouraging validity. Self- and peer-ratings converge well. OLIW converges well with aggregated play behavior ratings across 14 days.